The spectrum of beta thalassaemia mutations in the UAE national population. Issue 1 (January 1994) - Quaife, R; al-Gazali, L; Abbes, S; Fitzgerald, P; Fitches, A; Valler, D; Old, J M
Abstract : The beta thalassaemia alleles in 50 beta thalassaemia heterozygotes originating from many parts of the United Arab Emirates (UAE) have been characterised using the allele specific priming technique of the polymerase chain reaction (PCR). The IVSI-5 (G-->C) mutation was found to be present in 66%, while six other alleles occurred at the much lower frequencies of 2% to 8%. These were codon 8/9 (+G), IVSI-1, 3' end (-25 bp), codon 5 (-CT), IVSII-1 (G-->A), codon 30 (G-->C), and codon 15 (G-->A). The mutation types and percentages are compared with other Mediterranean Arab countries and neighbouring areas. It is proposed that IVSI-5 and other Asian Indian mutations were introduced into the UAE by population migration from the region previously known as Baluchistan. These findings should be useful for genetic counselling and the development of a first trimester prenatal diagnosis programme based on direct detection of mutations in the UAE.